Crushing analysis and multi-objective optimization of different length bi-thin walled cylindrical structures under axial impact loading. Issue 11 (2nd November 2019) - Dastjerdi, Ali Ahmadi; Shahsavari, Hamid; Eyvazian, Arameh; Tarlochan, Faris
ABSTRACT: This article attempts to increase the crashworthiness characteristics of energy absorbers. It is found that the effect of the bi-tubular arrangement on the energy absorption and peak force is nonlinear. This nonlinearity is somewhat related to friction but is mostly related to the changing of buckling modes. Therefore, it is possible to reach higher Specific Absorbed Energy (SAE) in the bi-tubular case than with two tubes since the weight is the same in both arrangements while the energy absorption is higher in the bi-tubular case. To exploit this, multi-objective optimization of bi-thin walled cylindrical aluminium tubes under axial impact loading is performed. The absorbed energy and the SAE are considered as the objective functions while the maximum crush load is regarded as a constraint. Finally, the optimal dimensions of tubes are found in order to maximize the SAE and energy absorption for a specified maximum crushing force.